‘The driest wainscots you are able to obtain’: The differentiated Dutch timber market before 1800 and the correlation between supply, demand and application (Bulletin KNOB, 2015)
Wainscoting was just one of the many products for sale on the Dutch timber market. A variety of sources would suggest that this was not primarily a case of thin, quartersawn oak planks around one centimetre thick, but much thicker, quarter-split, semi-finished products that were only later sawn into much thinner planks. A major reason for quarter sawing or splitting of logs was to mitigate warping. Finishings in particular required timber with a minimal tendency to split or bow and so wainscoting was often used for such work.There are several views on the etymology of the word ‘wainscot’. Based on the traded rather than the finished product, the suggestion that what we have here is a combination of ‘scot’ in the sense of panel with the prefix ‘wain’ (from ‘wane’), the side of the wood that still contains sapwood, merits further investigation. The wainscot timber exported from the regions of origin was, as far as can be ascertained from the sources, hardly ever ready for use. It generally took the form of split timber some 14 feet in length. The thickness could vary considerably, as is also clear from Dutch sources that talk of wainscoting up to several inches thick.The European trade in wainscoting was already huge by the fourteenth century. The greater part of this was transported to the province of Holland via the North Sea. Considerably smaller was the proportion of wainscoting rafted down the big rivers to the west. This trade doesn’t seem to have appeared until around the middle of the seventeenth century, when the Baltic trade had passed its peak. It is not yet possible to quantify the available data. But when harbours in the Baltic could no longer meet the demand from Holland, the trade in this particular product shifted to Bremen, to the Elbe and Rhine regions. Probably owing to the greater profitability, the export of wainscoting to England remained at a high level into the eighteenth century, while the prices paid at the Zaan timber auctions in the second half of the seventeenth century more than doubled. A possible partial explanation for the decline in the use of wainscoting in Dutch interiors is that the timber traders preferred to export their products to other markets where they could command a higher price.It would be interesting to conduct similar research for knee timber, floorboards, beams and other products. By considering the various timber elements of the past primarily as trading products rather than as finished products attuned to local conditions, it is possible to explain why timbers from different source areas are sometimes encountered within a single historical structural context, and how the use of such timbers was affected not only by changing tastes and fashions, but also by the supply stream from distant forests.